KONTRIBUSI KETERAMPILAN MENYIMAK TEKS LAPORAN HASIL OBSERVASI TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 2 BATANG KAPAS KABUPATEN PESISIR SELATAN - Tanjung, Jaka Ernasdi; Nursaid, Nursaid; Rasyid, Yulianti (Universitas Negeri Padang, 2019)
Abstract The purpose of this study was to describe: (1) the skill of listening to the text of the observation report, (2) the skill of writing observational report text, and (3) analyzing the contribution of observing the text of the observation report to the observation writing skills of the seventh grade students of SMP Negeri 2 Batang Kapas Pesisir Selatan Regency. The type of research used is quantitative and descriptive-analytical methods. The data collection technique was carried out through listening skills tests and test of observations texts of 45 people samples taken by proportional-random sampling. The results of the study showed: (1) writing skills of observational report text were in good qualification by achieving an average score of 81.84 in the range of values of 0 to 100, (2) the listening skill of observational report text were in a very good qualification achieving an average value of 90.00 in the range 0 to 100, and (3) the contribution of the skill of listening to the of observational report text to writing observational report text was equal to 31.03% among class VII students of SMP Negeri 2 Batang Kapas, Kabupaten Pesisir Selatan. Kata Kunci: Menyimak, Menulis, Kontribusi, Teks Laporan Hasil Observasi